Behind the backlash: Muslim Americans after 9/11 - Peek, Lori A. (Temple Univ. Press, 2011)
Peek chronicles the exclusion that Muslim American men and women faced before and especially in the aftermath of 9/11. Personal narratives describe the range of discrimination they experienced, the personal and collective impacts of the backlash, and the ways in which Muslims adapted in the aftermath of the terrorist attacks